The influence of particle size on some physicochemical, rheological and melting properties and volatile compound profile of compound chocolate and cocolin samples - Toker, Omer Said; Sagdic, Osman; Sener, Dilek; Konar, Nevzat; Zorlucan, Tugce; Daglioglu, Orhan (SPRINGER, 2016)
Compound chocolate and cocolin are widely used chocolate-derived products. However, we have not encountered any study about the influence of the particle size on the various quality parameters of these products. The aim of this study was to determine the effects of particle size on some physical (color properties, particle size distribution, rheology, microstructure and melting properties) and chemical properties (phenolic content, volatile composition and also FT-IR spectra of fats) of compound chocolate and cocolin samples. Refining level did not significantly affect color and melting properties, total phenolic content, thermal properties and FT-IR spectra of the fats extracted from the samples. D (90) values of compound chocolates and cocolins changed between 58.3-18.6 and 60.5-18.2 A mu m, respectively. Surface area of the samples also increased with refining process. Obtained rheological data were fitted to the Casson model with R (2) values ranged between 0.9863 and 0.999, and the corresponding parameters of the model, namely yield stress (tau (0)) and plastic viscosity (eta (pl)), significantly increased with decreasing particle size of the samples. Temperature sweep test was also performed, and temperature dependency of apparent viscosity of the samples changed with respect to refining process applied. Volatile composition of the samples was also determined by HS-SPME-GC/MS, and it concluded that both desired such as pyrazines and undesired such as acetic acid compounds for chocolate changed inversely proportional to particle size. According to the findings of the present study, it can be concluded that refining process and particle size are very substantial factors affecting the quality characteristics of the compound chocolate and cocolin samples.
Keywords: Compound chocolate; Cocolin; Phenolic; Rheology; Microstructure; Melting; Particle size; Volatile compounds; DARK CHOCOLATE; PALM STEARIN; BLENDS; FOOD; Food Science & Technology